Biogas production and nutrient recovery from biodegradation of swine manure - JosÃ de Souza Oliveira Filho (2016)
The production of renewable energy and fertilizer, through anaerobic biodegradation (AnBio) of waste from pig farming, presents itself as a strategic solution to minimize the negative effects associated with the large volume of manure generated in a small production space. However, further studies should be conducted to improve the understanding on the process and propose improvements. In this sense, this work was divided into three stages. In the first stage, a study was conducted to evaluate the changes that occur in organic matter and in organic and inorganic forms of nitrogen (N) and phosphorus (P) of the solid fraction of pig manure (PM) using anaerobic bench-top reactors as a function of seven hydraulic retention times (7, 14, 21, 28, 35, 42 and 49 days of biodegradation) and compared with the raw manure. In the second stage, we developed a study of anaerobic co-digestion, in a semi-continuous reactor, using the PM and the industrial waste of tomato processing (WTP) at different mixing ratios, to improve the performance of digestion and establish the best ratio of the two substrates for the production of biogas and methane. The following proportions were used (% PM + % WTP): 10% + 90%, 20% + 80%, 30% + 70%, 50% + 50% and 40% + 60%. In the third stage, there was an innovative study to recover the N present in the digestate generated after AnBio, using semipermeable membranes made of expanded polytetrafluoroethylene (PTFE) submerged in the material. This system consists of forcing the volatilization of N present in the digestate in the form of NH3 and then recover it in an acid solution of 1N H2SO4 flowing through the inside of the PTFE membrane. The N is recovered as the ammonium ion (NH4+), with potential for being used as fertilizer. Besides the digestate, raw pig manure (RPM) was used to compare the N recovery potential of both materials. The accumulation of the NH4+ formed was determined at nine sampling times (0, 7, 20, 30, 44, 54, 70, 79 and 93 hours). Based on the results obtained in the first stage, it was concluded that, during the digestion process, the organic matter of higher lability, represented by the carbon of the fulvic acid fraction and carbon oxidizable with 2.5 mL of H2SO4, was partially consumed, promoting the accumulation of recalcitrant organic matter at the end of the process. The contents of organic N and NH4+ reduced respectively by 45.2% and 54.2%, compared with their initial contents in the RPM, probably due to loss by volatilization. The P content reduced by 41.25% in relation to the initial content, due to the chemical precipitation of the inorganic fraction extractable in water with metallic cations within the reactor. In the case of co-digestion, increasing PM proportion to up to 30% of the feed mixture led to the maximum daily production of biogas (175 L) and the largest proportion of methane (60%). Amounts above 30% of manure in the mixture reduced biogas and methane production due to the increase of free NH3 concentration (272 mg L-1), which is toxic to most methanogens. As regards the recovery of N using PTFE membranes, it was observed that the recovery efficiency of the digestate was 12% higher compared with that observed in the RPM. Quantitatively, 4555 mg NH4+ could be recovered from the digestate in 93 hours of experiment, which can be used later as a source of N to agricultural crops.